1973
DOI: 10.1002/anie.197303561
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hysteresis and Its Cybernetic Significance

Abstract: The general foundations for a thermodynamic analysis of hysteresis phenomena in solutions and suspensions of polyelectrolyte systems are presented using examples of molecular hysteresis in biopolymers and membranes. The fundamental cybernetic significance of metastable states and molecular hysteresis for a physical interpretation of phenomena of life such as memory recording and biological rhythms is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 43 publications
(1 reference statement)
1
24
0
Order By: Relevance
“…) reduction of Z 2 , is unstable and can isomerize to Z 1 . When electron transfer is rapid compared to the structural change, reversible potentials E 1 and E 2 can be measured.…”
Section: Linkage Isomerizations Induced By Electrochemical Processesmentioning
confidence: 98%
See 1 more Smart Citation
“…) reduction of Z 2 , is unstable and can isomerize to Z 1 . When electron transfer is rapid compared to the structural change, reversible potentials E 1 and E 2 can be measured.…”
Section: Linkage Isomerizations Induced By Electrochemical Processesmentioning
confidence: 98%
“…Neumann [2] ®rst used the term``molecular hysteresis'' to describe the phenomenon which was hysteresis on precipitation and dissolution of the polymers in pH changes of aqueous solutions. However, because segments of the molecules interact, as do molecules in condensed form, the hysteresis he describes is still a collective phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric measurements have shown that polypeptides in viscous organic solvents may undergo intramolecular helix-coil transitions in the presence of electric fields (Schwarz and Seelig, 1968). In the meantime there are many reports on fieldinduced conformational chanoes in multi-stranded as well as in single-stranded polyelectrolytes (Neumann and Katchalsky, 1972;Neumann, 1973;Kikuchi andYoshioka, 1973, 1976;Yasunaga et al, 1973;Revzin and Neumann, 1974;Prrschke, 1974Prrschke, , 1976Prrschke, , 1985.…”
Section: Biopolymersmentioning
confidence: 99%
“…This assumption, known as the "quasi-steady-state hypothesis,"8 allows one to solve for the current distribution in a resistive-capacitive circuit representing the excitable membrane (see Appendix). 4 (1) where I is the current injected through the suction pipette. All those terms have been measured in previous experiments."…”
Section: Materials and Methods Experimental Studiesmentioning
confidence: 99%
“…Substituting (tu)n for (tu),1, in Equation 2 gives the recovery time for the (n+l)th beat (t)n+1, and thus (tU)n+, can be predicted, and so forth. If a dropped beat occurs, this allows for prolongation of the recovery time one full cycle and thus (4) where (tu), l is the latency of the last successful beat.…”
Section: Materials and Methods Experimental Studiesmentioning
confidence: 99%